2019
DOI: 10.1371/journal.pone.0215657
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and persistence of bacterial magnetite magnetosomes in a mammalian cell line: Implications for medical and biotechnological applications

Abstract: Magnetotactic bacteria biomineralize intracellular magnetic nanocrystals surrounded by a lipid bilayer called magnetosomes. Due to their unique characteristics, magnetite magnetosomes are promising tools in Biomedicine. However, the uptake, persistence, and accumulation of magnetosomes within mammalian cells have not been well studied. Here, the endocytic pathway of magnetite magnetosomes and their effects on human cervix epithelial (HeLa) cells were studied by electron microscopy and high spatial resolution n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…Although some surface degradation cannot be discarded, it seems that the MGs are more resilient toward degradation than the MNWs. The stability of MGs inside cancer cells has been reported before [ 30 , 35 ]. It is also notable from these TEM images that inside the endosomes, MGs could form chains and similar arrangements, as we had seen before in Figure 1 b, instead of being agglomerated in a dense cluster.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Although some surface degradation cannot be discarded, it seems that the MGs are more resilient toward degradation than the MNWs. The stability of MGs inside cancer cells has been reported before [ 30 , 35 ]. It is also notable from these TEM images that inside the endosomes, MGs could form chains and similar arrangements, as we had seen before in Figure 1 b, instead of being agglomerated in a dense cluster.…”
Section: Resultsmentioning
confidence: 85%
“…Therefore, if our magnetic nanostructures are compartmentalized inside endosomes, there is chance that they are also incorporated into the exosomes being released outside the cell. The incorporation of nanostructures inside endosomes has been frequently reported in the literature [ 29 , 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…We first preform migration assay in miR-199b-5p and CAV1, which proved that CAV1 had the ability to decrease migration. With respect to membrane localization of CAV1, we used TEM 5254 (transmission electron microscopy) to examine the membrane integrity after overexpression of LINC81507 in A549 cells. Compared with A549 control cell lines, A549 LINC81507-OE cell lines revealed less cell membrane damage and less alteration of cell wall structure by TEM (additional file.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 They are now considered amongst the best agents for magnetic hyperthermia, 23 photothermia 24,25 , and magnetic resonance imaging. 21,26,27 Besides, it was reported that magnetosomes display low toxicity, which has been due to their relatively insoluble magnetite core, [28][29][30] and furthermore, magnetosomes can have peroxidase-like properties that scavenge cytotoxic reactive oxygen species (ROS). 31,32 The question of the magnetosomes degradability however remains controversial, as a few studies also reported their progressive degradation over time, in protozoans, or in mice, 19,33,34 but not yet in human cells.…”
mentioning
confidence: 99%